Kids to kids on the Apple computer (for the Apple II, II+ and IIe) - Sanders, William B. 1944- (Datamost, 1984)
Young computer buffs explain how to use Basic to write fundamental programs for the Apple II, Apple II Plus, and Apple IIe computers and provide their favorite programs and games.